High Solar Desalination Efficiency Achieved with 3D Cu2ZnSnS4 Nanosheet‐Assembled Membranes. (25th August 2017) - Mu, Chunhong; Song, Yuanqiang; Deng, Kai; Lin, Shuai; Bi, Yutie; Scarpa, Fabrizio; Crouse, David
Abstract: Plasmonic structures are gaining tremendous interest due to their unique capability to trap light into subwavelength units, beneficial for high efficient light harvesting and related applications. Here, a plasmonic structure realized on a monocrystallized Cu2 ZnSnS4 (CZTS) nanosheet‐assembled membrane is presented. This unique CZTS structure exhibits high absorption efficiency (≈92.25%) in a broad solar spectrum (200–2500 nm), leading to a solar desalination efficiency of ≈84.5% under 1 Sun irradiation. This highly efficient broadband absorption is due to the structure induced localized surface plasmon resonance absorption. Besides, owing to its high chemical stability, salty water containing heavy metal ions can be effectively desalinated with a constant long time (>20 h) durability using this CZTS membranes as the absorber. The combination of the robust desalination effect, high stability and durability, as well as the low‐cost and scalable process for production, makes this type of CZTS membranes one of the most competitive desalination candidates. Abstract : Plasmonic Cu2 ZnSnS4 membranes assembled by ultrathin (≈6 nm) monocrystallized nanosheets with varying sub‐micrometer spatial gaps (0.1–0.6 µm) are synthesized. This unique structure induces surface‐plasmon‐resonance effect, leading to a high‐broadband absorption (≈92.25%) through 200–2500 nm, which in turn produces a high water evaporation rate of ≈1.46 kg m −2 h −1 under 1 Sun irradiation with long‐time durability.